Hs-CRP and Haptoglobin Levels in Iraqi Patients with Coronary Artery Disease - AL-Sa’adi, Warka’a T.; abdulmunem, Raed; Jasim, Hussam S. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Acute phase proteins which include C-reactive protein (CRP) and haptoglobin (Hp) are associated with inflammatory diseases such as injury, infection or malignancy, cardiovascular disease and obesity. Atherogenic index of plasma (AIP) evaluated as the atherogenicity index is correlated with different diseases.Objective : The study was to investigate hs-CRP and Hp concentration in Iraqi patients with coronary artery disease (CAD) and calculate AIP which predicts this disease.Subject and Method: The study included 64 subjects (39 patients with CAD and 25 healthy subjects as a control group). The markers of inflammatory hs-CRP and Hp levels were measured. Lipid profile (Total cholesterol TC, Triglyceride TG, High density lipoprotein HDLc, and Low density lipoprotein LDLc) was measured also. Atherogenic Index was calculated for both patients and control groups.Results: The study showed that there was a significant increase in hs-CRP and Hp concentrations in patients with CAD compared to healthy group. A significant increase in TC, TG and LDL was found in patients compared to control group. AIP values were (0.61±0.13) and (0.09±0.06) for patients and control groups respectively, showed high significant differences between the two groups.Conclusions: Results suggested that increasing concentration of hs-CRP and Hp in patients with CAD can be considered as a risk marker for the disease. Results of AIP concluded that it can provide information and predicate CAD disease.